Mahuang Fuzi Xixin Decoction Attenuates Th1 and Th2 Responses in the Treatment of Ovalbumin-Induced Allergic Inflammation in a Rat Model of Allergic Rhinitis - Mengyue Ren; Qingfa Tang; Feilong Chen; Xuefeng Xing; Yao Huang; Xiaomei Tan (Journal of Immunology Research)
Allergic rhinitis (AR) is one of the most common allergic diseases, which adversely affect patients’ quality of life. Mahuang Fuzi Xixin decoction (MFXD) has been widely used to treat AR in clinics in Asian countries. This study investigated the effect and possible therapeutic mechanisms of MFXD in the treatment of AR. A Wistar rat model of ovalbumin- (OVA-) induced AR was established and then treated with three doses of MFXD; AR symptoms, serum total immunoglobulin E, histamine, histopathological features, and release and expression of factors related to type 1 helper T (Th1) and type 2 helper T (Th2) responses were analyzed. Our study demonstrated that MFXD has a good therapeutic effect on OVA-induced allergic inflammation in an AR rat model as manifested in reduced frequencies of sneezing and nasal scratching and in reduced serum levels of total IgE and HIS. In addition, MFXD regulates imbalance in Th1/Th2 cells caused by AR by simultaneously attenuating Th1 and Th2 responses, such as by reducing the serum levels of IFN-γ and IL-4 and mRNA expression levels of IFN-γ, IL-4, GATA-3, and STAT-6. This study provided valuable information on the immunoregulatory effect of MFXD for the treatment of AR in future clinical studies.